Effect of Mechanical Activation on Leaching Behavior and Mechanism of Chalcopyrite. (19th May 2022) - Bai, Yunlong; Wang, Wei; Zhao, Shanrong; Lu, Diankun; Xie, Feng; Dreisinger, David
ABSTRACT: The leaching kinetics of chalcopyrite is sluggish due to the refractory nature of chalcopyrite and the formation of passive layers. In this study, the effect of mechanical activation on the leaching behavior and mechanism was studied by leaching tests, electrochemical measurements, particle size distribution analysis, scanning electron microscope (SEM), X-ray diffraction (XRD), differential scanning calorimetry-thermogravimetric analysis (DSC-TGA), X-ray photoelectron spectroscopy (XPS) and electron microprobe. The results show that mechanical activation can greatly promote the chalcopyrite leaching kinetics, and the copper extraction was increased from 14.1% to 55.7% and 91.8% after primary and secondary mechanical activation, respectively. The electrochemical study results indicated that mechanical activation did not change the cathodic reactions kinetics, however, the anodic dissolution kinetics was significantly promoted. XRD and DSC-TGA results show that mechanical activation treatment can effectively activate chalcopyrite due to the grain size reduction, formation of crystal defects and lattice deformation. The main solid product of chalcopyrite leaching is elemental sulfur. Besides particle size reduction, the reduction of grain size, formation of crystal defects and lattice deformation can increase the strain energy and instability of chalcopyrite, which plays an important role in improving chalcopyrite leaching kinetics.